2008
DOI: 10.1080/03057640802063486
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of examiner thinking during the process of examination marking

Abstract: Despite the abundant literature on educational measurement there has been relatively little work investigating the psychological processes underpinning marking. This research investigated the processes involved when examiners mark examination responses. Scripts from two geography A-level examinations were used: one requiring short and medium length responses and one requiring essays. Six examiners marked 50 scripts from each of the two examinations and were later asked to think aloud whilst marking four to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…However, these data collection approaches are imperfect. Some participants are better at thinking aloud than others and which can lead some participants to grade student work more slowly (Crisp 2008). Some participants in Department A said very little while they were assessing the work which suggests that they struggled to articulate their thinking.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…However, these data collection approaches are imperfect. Some participants are better at thinking aloud than others and which can lead some participants to grade student work more slowly (Crisp 2008). Some participants in Department A said very little while they were assessing the work which suggests that they struggled to articulate their thinking.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…The list of features was derived from our reading of the literature on examiner processes (Crisp, 2008;Pollitt & Murray, 1996;Suto & Greatorex, 2008;Suto & Nadas, 2009) as well as our scrutiny of the students' work. The judges were asked to "indicate the influence of the listed features when judging" using a five-point Likert scale from -2 ("Strong negative influence") to +2 ("Strong positive influence").…”
Section: Judging Processesmentioning
confidence: 99%
“…In particular, Yorke makes the point that 'assessors' grading behaviour is tacitly influenced by norm referencing and Vaughan (1991), Shay (2004), Delaney (2005) andOrrell (2008) also found that tutors draw on their knowledge of different students' work in order to make their judgements. More broadly, Crisp (2008) and found that other students' work affects individuals' standards' frameworks. There is no evidence that external examiners will not be influenced in the same way in making their judgements.…”
Section: External Examiners Can Represent Community Standards Reliablmentioning
confidence: 99%
“…Using the 'Heuristics and Biases' approach, research (Gilovich et al 2002) suggests that expert judgement in cases of uncertainty or complexity utilises a number of simplifying cues (heuristics) because a more rational and detailed judgement is too difficult or time consuming. Such heuristics allow for systematic biases to creep in of which the expert is unaware and may lead to assessors predicting performance in advance of completing reading (Crisp 2008). For example, recent research has identified that knowledge of the student, group stereotyping and surface features of work can be sources of bias (Brooks 2012;Kangis 2001;Hartley et al 2006).…”
mentioning
confidence: 99%